FRI0068 Diagnostic value of third generation anti-citrullinated peptides antibodies in rheumatoid artritis. (23rd January 2014) - Grados, D.; Riveros, A.; Martinez-Morillo, M.; Tejera, B.; Holgado, S.; Mateo, L.; Olivé, A.; Tena, X.; Teniente-Serra, A.; García-Lόpez, V.; Ruíz, E.; Martínez-Cáceres, E.
Abstract : Background: Assays that detect anti-citrullinated peptides antibodies (ACPA) are considered to be more specific than rheumatoid factor in the diagnosis of rheumatoid arthritis (RA). Several tests have been developed using different antigens: first, second and third-generation cyclic-ACPA (CCP1, CCP2, CCP3) and modified citrullinated vimentin (MCV). Objectives: To investigate anti-CCP3 in a group of patients positive citrullinated vimentin antibodies (MCVA). Methods: The retrospective study was done at the university hospital with a reference population of 800, 000. Atotal of 259 patients positive for IgG MCV antibodies (by ELISA) attending the outpatient rheumatology clinic were tested for anti-CCP3 (by ELISA). From the total, 182 (70.3%) of them had a rheumatic disease: RA in 121 (66.5%) and other: elderly-onset arthritis, non-filiated arthritis, connective, vasculitis, Still's disease, espondiloarthritis, microcrystalline arthritis, polymyalgia rheumatica and sarcoidosis, in 61 (33.5%). There are 77 (29.7%) patients with other conditions (non rheumatic disease) positive for MCVA were also tested for anti-CCP3. Results: From the 121 RA patients, 106 (87.6%) were positive for anti-CCP3. In contrast, only 15 (24.6%) of the 61 patients without RA and only 4 (5.2%) of the 77 MCVA positive patients with no rheumatic disease associated were CCP3 positive. Interestingly, within the group no RA, of the 13 patients with anti-CCP3 values >60 U/ml, 6 (46.2%) were patients with palindromic rheumatism and two of them had developed RA. Specificity of anti-CCP3 for RA as compared to other rheumatic disease was 76.7%, that raised to 86.9% when comparing RA versus to non-RA (with or without another rheumatic disease). Positive and negative predictive values of anti-CCP3 for RA were 85.5% and 88.8%, respectively whereas positive predictive values for anti-MCV was 39.1%. Conclusions: Anti-CCP3 antibodies show a higher specificity for RA when compared to MCVA with a better positive predictive values, a crucial feature for a test in use for clinical practice. Disclosure of Interest: None Declared